Predictive simulation of non-steady-state transport of gases through rubbery polymer membranes. (3rd January 2018) - Soniat, Marielle; Tesfaye, Meron; Brooks, Daniel; Merinov, Boris; Goddard, William A.; Weber, Adam Z.; Houle, Frances A.
Abstract: A multiscale, physically-based, reaction-diffusion kinetics model is developed for non-steady-state transport of simple gases through a rubbery polymer. Experimental data from the literature, new measurements of non-steady-state permeation and a molecular dynamics simulation of a gas-polymer sticking probability for a typical system are used to construct and validate the model framework. Using no adjustable parameters, the model successfully reproduces time-dependent experimental data for two distinct systems: (1) O2 quenching of a phosphorescent dye embedded in poly( n -butyl(amino) thionylphosphazene), and (2) O2, N2, CH4 and CO2 transport through poly(dimethyl siloxane). The calculations show that in the pre-steady-state regime, permeation is only correctly described if the sorbed gas concentration in the polymer is dynamically determined by the rise in pressure. The framework is used to predict selectivity targets for two applications involving rubbery membranes: CO2 capture from air and blocking of methane cross-over in an aged solar fuels device. Graphical abstract: Image 1 Highlights: Permeation and transport of gases in rubbers simulated with no fitting parameters. Model validation using transport measurements under variable pressure conditions. Molecular dynamics simulations used to assess facile CO2 uptake by PDMS. Interpretation of literature phosphorescent gas sensor data using full photophysics. Evaluation of permselectivity targets for CO2 capture and conversion applications.